CONJUNCTION ERROR ANALYSIS ON INDONESIAN EFL UNIVERSITY STUDENTS’ WRITTEN COMPOSITIONS: A QUALITATIVE STUDY - Wibawati, Riska Tulus; Musthafa, Bachrudin (Universitas Pendidikan Indonesia, 2019)
It has been widely agreed that conjunction constitutes one important aspect in building cohesion. Despite the fact, the use of conjunction in both EFL and ESL students’ writings is deemed problematic. Some problems found by quantitative researchers cover misuse, overuse and underuse. Some others revealed by qualitative researchers involve misuses but with specific aspects like meaning and register. The types of errors mentioned were also found in Indonesian context. This study aims at investigating qualitatively the conjunction errors committed by Indonesian EFL university students in their written compositions. This study revealed that distraction, wrong relation and semantic incompletion are respectively the most frequently committed errors. Further research examining the major problems constituting the main cause of the error occurrences need to be conducted.